The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/polym14051039
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Analysis of Silica/PMMA Interface Shear Behavior

Abstract: The mechanical properties of cementitious materials injected by epoxy have seldom been modeled quantitatively, and the atomic origin of the shear strength of polymer/concrete interfaces is still unknown. To understand the main parameters that affect crack filling and interface strength in mode II, we simulated polymethylmethacrylate (PMMA) injection and PMMA/silica interface shear deformation with Molecular Dynamics (MD). Injection simulation results indicate that the notch filling ratio increases with injecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…For epoxy/SiO 2 systems, various polymeric materials have been investigated using MD simulations. Min and co-workers , used pulling and sliding MD simulations and a hybrid force field to investigate the interfacial adhesion of polyimides (PIs) on an amorphous SiO 2 model by combining INTERFACE FF and ReaxFF . Pulling (tensile) and sliding (shear) actions correspond to deformation in modes I and II, respectively.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…For epoxy/SiO 2 systems, various polymeric materials have been investigated using MD simulations. Min and co-workers , used pulling and sliding MD simulations and a hybrid force field to investigate the interfacial adhesion of polyimides (PIs) on an amorphous SiO 2 model by combining INTERFACE FF and ReaxFF . Pulling (tensile) and sliding (shear) actions correspond to deformation in modes I and II, respectively.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Pei et al 43 also studied the effect of CAs on PP/GF composites through MD simulations of mode I and II deformations and confirmed that the shear strength increased noticeably with increasing CA surface density. Ji et al 44 performed MD simulations for poly(methyl methacrylate) (PMMA) on a shaped SiO 2 surface exhibiting a slit cavity. Importantly, they demonstrated that the cavityfilling ratio affected the stress magnitude required for sliding deformation.…”
Section: Simulations Of Adhesion Between Sio 2 Substrates and Polymer...mentioning
confidence: 99%
See 1 more Smart Citation